1981
DOI: 10.1128/iai.32.3.1084-1092.1981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunogenic outer membrane proteins of Haemophilus influenzae type b in the infant rat model system

Abstract: Outer membrane proteins of Haemophilus influenzae type b which are immunogenic in infant rats were identified by a radioimmunoprecipitation method. Intact cells of H. influenzae type b were radioiodinated by a lactoperoxidase-catalyzed procedure, and an outer membrane-containing fraction was prepared from these cells. These radioiodinated outer membranes were mixed with sera obtained from rats convalescing from systemic H. influenzae type b disease induced at 6 days of age, and the resultant (antibody-outer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 30 publications
3
81
0
Order By: Relevance
“…1). The heavy component had a buoyant density of 1.22 g/cm3, which is similar to the buoyant densities of the outer membranes of other gram-negative bacteria (7,20), including P. haemolytica (26), and the light component had a buoyant density of 1.12 g/cm3. Analysis of both heavy and light components by SDS-PAGE showed that the protein profiles of the heavy and light components were different (Fig.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…1). The heavy component had a buoyant density of 1.22 g/cm3, which is similar to the buoyant densities of the outer membranes of other gram-negative bacteria (7,20), including P. haemolytica (26), and the light component had a buoyant density of 1.12 g/cm3. Analysis of both heavy and light components by SDS-PAGE showed that the protein profiles of the heavy and light components were different (Fig.…”
Section: Resultssupporting
confidence: 56%
“…A 5-ml sample of this culture harvested by centrifugation twice at 20,000 x g for 10 min each time at 4°C and washed in phosphate-buffered saline (PBS) (0.01 M PBS, 0.85% NaCl, pH 7.2) was suspended in 1 ml of PBS. P. multocida cells were labeled with the lactoperoxidase-catalyzed radioiodination method (7). Labeled cells were sus-pended in PBS to a specific activity of 2 x 108 cpm/ml and used immediately in RIP experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature suggests that M. pneumoniae stimulates cellular, humoral, and secretory immune responses (13,18,(38)(39)(40)(41), we chose to examine the host humoral response to specific mycoplasma proteins. The RIP technique, previously shown to be a powerful tool for analyzing the immune response to proteinaceous immunogens of pathogens (29,30,32,(42)(43)(44), was used to examine acute and convalescent human and hamster sera. Preinfection hamster and acute human sera usually precipitate a small number of mycoplasma proteins in the soluble-antigen RIP assay.…”
Section: Discussionmentioning
confidence: 99%
“…The Hib strains used in this study were obtained from pediatric research centers located throughout the United States and have been described previously (9). Bacterial media (brain heart infusion [BHI; Difco Laboratories, Detroit, Mich.] supplemented with Levinthal base [BHIs] [1]) and growth conditions have been described previously (13). Hib strains were stored at -70°C in a mixture of equal parts of glycerol and BHI.…”
Section: Methodsmentioning
confidence: 99%